HUBUNGAN FAKTOR KARAKTERISTIK PEKERJA, SAFETY MORNING TALK (SMT) DAN HOUSEKEEPING DENGAN KEJADIAN MINOR INJURY PADA PEKERJA DI PROYEK PEMBANGUNAN GEDUNG KANTOR PT. X JAKARTA - Wahid Kurniawan; Yuliani Setyaningsih; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
A workplace accident is an unexpected and undesired event that can cause in loss of time, property and casualties occurring within an industrial work process. The highest occupancy rate in the construction sector compared to other sectors accounted for 30% of the total number of accidents. Based on accident report at Project PT. X, minor injury events such as material pinched, injured due to material, work accident on the eyes due to dust that cause minor injuries such as wounds / tears include in the high category. The implementation of Safety Morning Talk and Housekeeping has been carried out regularly, and there should be no workplace accidents. This study aims to analyze the relationship of Worker Characteristic Factors, Safety Morning Talk (SMT) and Housekeeping with minor injury events to workers in the Construction Project of PT.X. Type of this research is analytical by cross sectional method. Samples in this research are 49 from 94 workers with slovin formulas. The sampling technique used proportionate stratified random sampling technique in 3 part of work section. Data is collected by questionnaire and observation checklist for obedience of workers and housekeeping. Based on the results of research by using Partial Least Square (PLS), the dependent variables with enforcement are characteristic of workers and housekeeping, the dependent variables with minor injury are enforcement of workers. Meanwhile, the independent variables with enforcement are Safety Morning Talk. The researchers suggest to the company to create Housekeeping Day and give a reward for workers is an example.